RORα is crucial for attenuated inflammatory response to maintain intestinal homeostasis - Oh, Se Kyu; Kim, Dongha; Kim, Kyeongkyu; Boo, Kyungjin; Yu, Young Suk; Kim, Ik Soo; Jeon, Yoon; Im, Sun Kyoung; Lee, Su Hyung; Lee, Ji Min; Ko, Younhee; Lee, Ho; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Retinoic acid-related orphan receptor α (RORα) functions as a transcription factor for various biological processes, including circadian rhythm, cancer, and metabolism. Here, we generate intestinal epithelial cell (IEC)-specific RORα-deficient (RORαΔIEC) mice and find that RORα is crucial for maintaining intestinal homeostasis by attenuating nuclear factor κB (NF-κB) transcriptional activity. RORαΔIEC mice exhibit excessive intestinal inflammation and highly activated inflammatory responses in the dextran sulfate sodium (DSS) mouse colitis model. Transcriptome analysis reveals that deletion of RORα leads to up-regulation of NF-κB target genes in IECs. Chromatin immunoprecipitation analysis reveals corecruitment of RORα and histone deacetylase 3 (HDAC3) on NF-κB target promoters and subsequent dismissal of CREB binding protein (CBP) and bromodomain-containing protein 4 (BRD4) for transcriptional repression. Together, we demonstrate that RORα/HDAC3-mediated attenuation of NF-κB signaling controls the balance of inflammatory responses, and therapeutic strategies targeting this epigenetic regulation could be beneficial to the treatment of chronic inflammatory diseases, including inflammatory bowel disease (IBD).
Keywords: Animals; Epigenesis, Genetic; Epithelial Cells; Female; Homeostasis; Inflammation; Intestines; Mice; Mice, Inbred C57BL; NF-kappa B; Orphan Nuclear Receptors; Transcription Factors; Transcription, Genetic; Transcriptome; Epigenetic regulation; HDAC3; Inflammation; NF-kB signaling; RORα